2014
DOI: 10.5798/diclemedj.0921.2014.04.0509
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of single port thoracoscopic approach in pleural effusions

Abstract: Objective: Currently, thoracoscopic procedures have been used frequently in diagnosis and treatment of pleural effusions. It was reported, high diagnosis and treatment success with thoracoscopy in pleural effusion, which was not, diagnosed using cytology and blinding pleural biopsy procedures. In this study, it was aimed to evaluate of the patient was performed video-assisted thoracic surgery (VATS) due to pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In the study of Kurkcuoglu et al, the diagnostic success rate of VATS was found to be 97.9% (4). In the study of Buyukkarabacak et al on pleural effusions with a single port VATS approach, an accuracy of 100% was found in the malignancy group (5). Confirming the above studies, we found the correct diagnosis rate to be 100% in pleural biopsies performed with Uniportal VATS.…”
Section: Total Totalsupporting
confidence: 84%
See 3 more Smart Citations
“…In the study of Kurkcuoglu et al, the diagnostic success rate of VATS was found to be 97.9% (4). In the study of Buyukkarabacak et al on pleural effusions with a single port VATS approach, an accuracy of 100% was found in the malignancy group (5). Confirming the above studies, we found the correct diagnosis rate to be 100% in pleural biopsies performed with Uniportal VATS.…”
Section: Total Totalsupporting
confidence: 84%
“…When the literature is evaluated in terms of the pathology results of the pleural tissue obtained during the operation, it is seen that there are series with quite different weights for the rates of benign and malignant diseases. It has been published in different series that a varying range of malignancies was detected with a rate of 15-53% (4,5,8,9). In our study, malignant pleural tissue results were encountered with 36%.…”
Section: Total Totalsupporting
confidence: 53%
See 2 more Smart Citations